New genomic features of the polled intersex syndrome variant in goats unraveled by long‐read whole‐genome sequencing. (14th February 2020) - Simon, R.; Lischer, H. E. L.; Pieńkowska‐Schelling, A.; Keller, I.; Häfliger, I. M.; Letko, A.; Schelling, C.; Lühken, G.; Drögemüller, C.
Summary: In domestic goats, the polled intersex syndrome (PIS) refers to XX female‐to‐male sex reversal associated with the absence of horn growth (polled). The causal variant was previously reported as a 11.7 kb deletion at approximately 129 Mb on chromosome 1 that affects the transcription of both FOXL2 and several long non‐coding RNAs. In the meantime the presence of different versions of the PIS deletion was postulated and trials to establish genetic testing with the existing molecular genetic information failed. Therefore, we revisited this variant by long‐read whole‐genome sequencing of two genetically female (XX) goats, a PIS‐affected and a horned control. This revealed the presence of a more complex structural variant consisting of a deletion with a total length of 10 159 bp and an inversely inserted approximately 480 kb‐sized duplicated segment of a region located approximately 21 Mb further downstream on chromosome 1 containing two genes, KCNJ15 and ERG . Publicly available short‐read whole‐genome sequencing data, Sanger sequencing of the breakpoints and FISH using BAC clones corresponding to both involved genome regions confirmed this structural variant. A diagnostic PCR was developed for simultaneous genotyping of carriers for this variant and determination of their genetic sex. We showed that the variant allele was present in all 334 genotyped polled goats of diverse breeds and that all analyzed 15 PIS‐affected XX goats were homozygous. Our findings enable for the first time a precise genetic diagnosis for polledness and PIS in goats and add a further genomic feature to the complexity of the PIS phenomenon.